The evolution of competitive conditions in the US banking sector - Δράκος Κωνσταντίνος (SPOUDAI Journal of Economics and Business, 2004)
In this paper competitive conditions in the US banking sector are studied on the basis of a comprehensive State-level dataset for 1966-2000. Our findings are twofold. First, we empirically document that throughout the period studied the US banking sector's behaviour is consistent with a monopolistically competitive market structure. Second, the evolution of the market reveals that competitive conditions in the 90's have considerably weakened. JEL Classification: C33, D43, G21